Smoking and Hepatitis B Virus–Related Hepatocellular Carcinoma Risk: The Mediating Roles of Viral Load and Alanine Aminotransferase. Issue 4 (19th February 2019) - Wang, Ya‐Hui; Chuang, Ya‐Hui; Wu, Chih‐Feng; Jan, Meng‐Chin; Wu, Wan‐Jung; Lin, Chih‐Lin; Liu, Chun‐Jen; Yang, Ya‐Chien; Chen, Pei‐Jer; Lin, Shi‐Ming; Tsai, Mong‐Hsun; Huang, Yi‐Wen; et al.
Abstract : Smoking interacts with hepatitis B virus (HBV) to increase the risk of hepatocellular carcinoma (HCC), which might be explained by its role in antiviral immunity. We evaluated the potential mediating role of viral load and/or alanine aminotransferase (ALT) in the relation of smoking with HBV‐associated HCC risk. Using multiple mediation analyses to analyze data from 209 HCC cases and 1, 256 controls nested within a cohort of 4, 841 male HBV carriers, we found that the effect of smoking on the risk of subsequent HCC was substantially mediated through viral load (percent mediated, 31.7%; P = 0.0054), and a significant mediation effect by both viral load and ALT was also evidenced. Among the 1, 143 subjects with repeated measures of viral load and ALT over periods of up to 16 years, we further observed that a higher number of pack‐years of smoking was associated with higher viral load, maintenance of a high viral load (>4.39 log copies/mL), more severe hepatotoxicity grade, and increased likelihood of ALT ≥80 U/L (odds ratio, 3.14; 95% confidence interval, 1.03‐9.64; odds ratio, 6.06; 95% confidence interval, 1.10‐33.25, respectively, for 10‐19 and ≥20 pack‐years versus nonsmokers) during follow‐up. Furthermore, plasma interferon‐γ levels were reduced in smokers compared with nonsmokers (interferon‐γ‐positive rate, 14.9% versus 28.7%; P < 0.0001) at baseline. Smoking was also associated with a reduced natural killer (NK) cell frequency in peripheral blood, characterized by reduced NK function through a systems immunology approach, after long‐term follow‐up in a subsample (n = 171). The combination of smoking and reduced NK cell frequency further increased viral load and the likelihood of ALT ≥80 U/L. Conclusion : The data highlight a role of smoking in HBV viral load, underlining the importance of smoking prevention and cessation in hepatitis B management.